Copper-Catalyzed Aerobic Oxidative Trifluoromethylation of H-Phosphonates Using Trimethyl(trifluoromethyl)silane - Chu, Lingling; Qing, Feng-Ling (Synthesis, 2012)
Copper-catalyzed aerobic oxidative trifluoromethylation of readily accessible H-phosphonates was demonstrated for the first time. This method not only provides an alternative method for the facile synthesis of a series of biologically important CF3-phosphonates, but also demonstrates the first example of the efficient construction of a P–CF3 bond via transition-metal catalysis.
Keywords: copper catalysis; phosphonates; trifluoromethylation